Fungsi Zikir Bordah sebagai Relasi Sosial dan Budaya Masyarakat Labuhanbatu - Suriani Suriani; Ramuddin Yakup Hasibuan; Rika Afianti (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This paper discusses the Bordah Zikir tradition which is still maintained by a small group of Labuhan Batu people. Bordah zikir has become part of the culture of the Malay Community in Labuhan Batu that used to maintaining social relations between them. This tradition is carried out in various events such as weddings, circumcisions, and also MTQ activities. With a traditional form that is considered classic, how can Bordah Zikir be able to continue to exist in the current era? What role does this art offer so that it can become one of the social relations activities for the Labuhan Batu community? The approach of this paper is sociological-historical which sees the current reality of the Bordah Zikir tradition through the historical pulls understood by the Labuhan Batu community. The results of the study show that Bordah zikir has a very high social function for the Labuhan Batu community. This function is related to the relationships that are built between communities towards an attitude of togetherness as well as contemplation of the soul to become a better person. This is because the understanding in Bordah's recitation itself contains the history of the Prophet Muhammad's journey to be able to reflect on the whole Labuhan Batu community in the form of rhythmic art.